POTENSI EKONOMI PADA KOLONG BEKAS PENAMBANGAN TIMAH DI KABUPATEN BANGKA, PROVINSI BANGKA BELITUNG - Oot Hotimah (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2015)
The development of the tin mining industry in Bangka Bangka Belitung has contributed very significantly to the economy of communities in the region. But on the other hand, these activities also have a negative effect in the form of reduced mangrove forests, destruction of soil, polluted water sources, as well as the emergence of pits (pit) excavated and others. So far under the utilization of tin in Bangka Island is not optimal. Economically, the potential pit can be used as a source of raw water, aquaculture, or recreational water. This can be done through environmental reclamation. Technically goal of rehabilitation is to restore the soil conditions for stable and not prone to erosion. From the economical and aesthetic aspects of land, soil conditions improved so that the value or economic potential can be restored at least its original state. From the aspect of the ecosystem, ecosystem condition to attempt the return of the original ecosystem.